8-substituted pyrido[3,4-d]pyrimidin-4(3H)-one derivatives as potent, cell permeable, KDM4 (JMJD2) and KDM5 (JARID1) histone lysine demethylase inhibitors - Bavetsias, V; Lanigan, R; Ruda, G; Atrash, B; McLaughlin, M; Tumber, A; Mok, N; Le Bihan, Y; Dempster, S; Boxall, K; Jeganathan, F; Hatch, S; et al. (American Chemical Society, 2016)
We report the discovery of N-substituted 4-(pyridin-2-yl)thiazole-2-amine derivatives and their subsequent optimization, guided by structure-based design, to give 8-(1H-pyrazol-3-yl)pyrido[3,4-d]pyrimidin-4(3H)-ones, a series of potent JmjC histone N-methyl lysine demethylase (KDM) inhibitors which bind to Fe(II) in the active site. Substitution from C4 of the pyrazole moiety allows access to the histone peptide substrate binding site; incorporation of a conformationally constrained 4-phenylpiperidine linker gives derivatives such as 54j and 54k which demonstrate equipotent activity versus the KDM4 (JMJD2) and KDM5 (JARID1) subfamily demethylases, selectivity over representative exemplars of the KDM2, KDM3, and KDM6 subfamilies, cellular permeability in the Caco-2 assay, and, for 54k, inhibition of H3K9Me3 and H3K4Me3 demethylation in a cell-based assay.